Isolasi dan Karakterisasi Fungi Endofit Umbi Porang (Amorphophallus muelleri Blume) sebagai Antibakteri - Muhammad Fazrul Rahman; Witiyasti Imaningsih; Sasi Gendro Sari (Bioscientiae, 2017)
Medicinal plants such as porang (Amorphophallus muelleri Blume) can produce bioactive compounds from plants-associated endophytes. Therefore, medicinal plants were a sources of isolation of endophytic fungi and endophytic fungi were a sources of secondary metabolites that have anticancer, antimalarial, antimicrobial, and so on. A Porang tuber has been used as a medicine for boils, medicine for sliced wounds and medicine for wounds due to venomous animal bites. The research was aimed to carry out isolation and characterization of endophytic fungi from porang tuber, and to test the ability of endophytic fungi from porang tuber as antibacterial against gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria. Isolation of endophytic fungi from porang tubers succeeded in getting five different fungi isolates. Based on macroscopic and microscopic characteristics, endophytic fungi isolated from porang tuber were members of the genus Curvularia, Penicillium, 2 isolates of Aspergillus, and 1 isolate that had not been identified. Porang endophytic fungi had antibacterial activity against S. aureus, but did not have antibacterial activity against E. coli bacteria. Endophytic fungi that had antibacterial activity were Curvularia sp., Penicillium sp., Aspergillus sp.